2000
DOI: 10.1046/j.1537-2995.2000.40111308.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of bacteria in inoculated platelets: implications for bacteria detection and the extension of platelet storage

Abstract: These experiments suggest that an assay capable of detecting 10(2) CFU per mL on Day 3 of storage would detect the vast majority of bacterially contaminated platelet units, prevent many cases of platelet-associated bacterial sepsis, and provide a scientific basis for the extension of the current platelet storage time. It would be expected that a rare, slow-growing organism could escape such a detection scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 6 publications
4
131
0
Order By: Relevance
“…It is estimated that the level of contamination at the time of collection is generally relatively low, probably on the order of 1-10 colony forming units/mL or less. 26 Once the product is contaminated, the inoculated bacterial seed can proliferate within hours to reach levels of 10 6 /mL or greater. Such quantities of bacteria infused with the transfusion product over a short period of time can cause bacteremia that may progress to sepsis and death.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that the level of contamination at the time of collection is generally relatively low, probably on the order of 1-10 colony forming units/mL or less. 26 Once the product is contaminated, the inoculated bacterial seed can proliferate within hours to reach levels of 10 6 /mL or greater. Such quantities of bacteria infused with the transfusion product over a short period of time can cause bacteremia that may progress to sepsis and death.…”
Section: Clinical Relevancementioning
confidence: 99%
“…For most bacterial species, growth in platelet units can occur, rapidly reaching log phase within 24-48 hours. 12,26 An exception is the common skin contaminant, Staphylococcus epidermidis which is a slower growing organism and usually reaches the log phase in 48-72 hours. Since this and similar organisms account for a large proportion of the bacterial species found to contaminate blood units, such slower growth characteristics need to be considered when optimizing sampling strategies for bacterial detection.…”
Section: Prevention Of Bacterial Proliferationrefrigeration Of Platelmentioning
confidence: 99%
“…Species identification and differentiation is troublesome due to the bacteria's slow and fastidious growth. At the time of blood collection, the level of contamination is between 1 to 10 colony forming units/mL thus justifying the failure to isolate or amplify the bacterium DNA in blood samples after one-round amplifications (BRECHER et al, 2000). In our country, none of the few commercial kits, either serological or based on histochemical techniques, are currently available in routine laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of a 12-year study, where adverse septic reactions after platelet transfusions were analyzed, showed that an increase in transfusing apheresis platelet concentrates was accompanied by a decrease in such reactions (39). Other studies have confirmed these observations pointing to the fact that bacterial contamination of pooled red blood cell concentrates is higher than in those collected from one donor (40). Yet, the findings of another paper described more bacterial contaminations in apheresis concentrates (49).…”
Section: Preventionmentioning
confidence: 98%
“…Yet, the infection is asymptomatic in most cases. Thus, such donors are a potential source of blood component contamination (40,41). Transfusion associated bacterial sepsis may be caused by other intestinal pathogens, such as Campylobacter jejuni and Salmonella Heidelberg, which induce donor's bacteremia (18).…”
Section: Sources Of Blood Components Bacterial Contaminationmentioning
confidence: 99%